STUDI IMPLEMENTASI NILAI-NILAI HAM DALAM PERATURAN DAERAH DAN DAMPAKNYA BAGI PEMENUHAN HAK EKONOMI, SOSIAL DAN BUDAYA DI KABUPATEN BANTUL PROVINSI DIY - Nanik Prasetyoningsih; Mujiyana S.H., M.H.; Septi Nur Wijayanti (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Human rights conditions still have not significant progress yet. It will be shown in the absence of serious measures and well-planned by the government for the fulfillment of human rights both in the field of economic, social and cultural as well as in the field of civil and political rights. This research was conducted to describe the problems as follows: (1) How is the process of formulating the values of human rights in the draft of local regulations?, and (2) What is the impact of local regulations in the fulfillment of ESC rights of citizens? The aims of the study are: identify and assess the process of formulating the values of human rights in the draft regulations, and the impact of local regulations in the fulfillment of ESC rights. This is a normative legal research, its find the truth based on the logic of the legal thougth. The analysis conducted on the laws and regulations, which its containing norms of protection and fulfillment of ESC rights. In terms of empirical conducted to assess the impact of the local regulation on the community. The research conclusion are the Government District of Bantul have included ESC rights values into ones that are made in the period 2005-2009, although not all values can be accommodated into the local regulation. Regulation set a positive impact in the effort to fulfill the responsibility of the local government in fulfillment and protection of ESC rights.